Investigating the Role of Education on Rice Waste Management with Emphasis on Environmental Protection and Health - Mohammadreza Shiran; Mehdi Charmchian Langerodi; Leila Najafian; Fatemeh Khaleghi (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Waste accumulation has very negative impacts on human health and the environment, but if managed properly, it can help in increasing food safety of the community. Agricultural extension and education as one of the main pillars of modern agriculture can play an effective role in agricultural productivity and waste and in general improve the living conditions of farmers. The purpose of this study was to investigate the role of education on rice waste management in Sari, Iran with emphasis on environmental protection and health. Materials and methods: This structural equation-based correlational survey was performed in 290 rice cultivators in Sari, north of Iran. The participants were selected based on Cochran's formula. Data were collected using a researcher-made questionnaire. Based on the average variance extracted (0.506 >AVE< 0.581) and composite reliability (0.946 >CR < 0.953), the questionnaire had convergent validity and appropriate reliability. SPSS V16 and SmartPLS 2.0.M3 were used to analyze the data. Results: The study showed that trainings on the use of straw and other residues of rice positively affects rice waste management operations and is linked to environmental protection and better health status. Conclusion: Without knowledge of rice waste management operations and proper trainings, rice cultivators cannot be expected to succeed in waste management while considering environmental protection and health.